The Writing of “Dreck”: Consumerism, Waste and Re-use in Donald Barthelme’s Snow White - Rachele Dini (European Journal of American Studies)
This paper examines the relationship between material waste, late capitalism, and the language and structure of Donald Barthelme’s fiction, with particular attention to Snow White (1967). Going against established modes of allegorizing the theme of waste in Barthelme’s work, I suggest the fruitfulness of a literal reading, and propose that his waste objects are framed as inevitable outcomes of a successful advertising campaign. They are the physical evidence or counterpart to the lexicons of marketing and advertising that so preoccupied the author. Such a reading is particularly apt given that Barthelme’s early fiction coincided with the birth of the environmental movement, and builds on recent scholarship in the fields of New Materialism and waste studies. By examining Barthelme’s depictions of waste through the dual lens of New Materialism and waste studies, and in relation to the work of his contemporaries as well as the literary experimentations of earlier avant-gardists, the paper establishes the different ways in which Barthelme articulates value.